Computational study on allostery in bacterial ribosome - Yıldırım, Hatice Zeynep. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Molecular machines in a cell have signal processing to perform their function using specific sites such as active or allosteric sites. Ligand binding to active sites or signal transferring from allosteric sites affect their function and dynamics. In this thesis, firstly crystal structure of bacterial ribosome (4kdk-4kdj) and its conformers which are generated by ClustENM are investigated to determine allosteric communication pathways. Targets on ribosome are determined as the Decoding Center (DC) – the Sarcin Ricin Loop (SRL), DC - the Peptidyl Transferase Center (PTC) and the PTC – Tunnel. On the allosteric pathways between DC and SRL, EF-G stands out with critical sites on its domains IV which has a significant function in blocking back translocation of tRNA. Some significant nucleotide and aminoacid like A1493 and Met580 appear on pathways between DC-SRL, which help EF-G hydrolysis. On the DC-PTC pathways drug binding site is observed. On the PTC-ribosomal tunnel pathway has a highly conserved non-Watson-Crick base pair and binding pocket for antibiotic is found. Secondly, the bacterial ribosome of E.coli, 4v5h, is analyzed to investigate allostery between Secretion Monitor (SecM)–PTC and TF-Ribosomal Tunnel. A76 of tRNA and nascent chain which consists of alanines seems significant between U2585 and A2451 to provide allosteric communication between SecM and PTC. On the shortest pathways on the TF-Ribosomal Tunnel, GLY91 from L22 has a high frequency of occurrence on all pathways. GLY91 is significant for elongation arrest and for the turn of the β-hairpin of L22 which is important since antibiotic resistance appears when a mutation on the β-hairpin occurs.
Keywords: Allosteric regulation.; Allosteric proteins.; Microbial respiration -- Mathematical models.